The Influence of Leadership Style and Job Training On Employee Performance in the Cement Industry - Diah, Zulfikar Mohamad; Qomariah, Nurul; Herlambang, Toni (Budapest International Research and Critics University, 2024)
Employee performance is very important for the survival of an organization. This is because individual employee performance will have an impact on organizational performance. The purpose of this research is to determine and analyze the influence of leadership style variables and job training on employee performance at PT. Imasco Asiatic Cement Jember. The population in this study includes all 234 employees of the PT Semen Imasco Asiatic Jember factory. The minimum number of samples taken was 117 respondents, which is 50% of the total 234 employees. Descriptive analysis is used to explain respondents' descriptions in this research. Validity tests and reliability tests are also used so that the questionnaire used is valid and reliable. Hypothesis testing to determine the impact of the independent variable on the dependent variable. The results of this research show that leadership style and job training have a positive and significant impact on employee performance at PT. Imasco Asiatic Cement Jember.